Mid-life job insecurity associated with subjective well-being in old age: results from the population-based MONICA/KORA study - Amira Barrech; Jens Baumert; Rebecca T Emeny; Harald Gündel; Karl-Heinz Ladwig (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVE: This study aimed to examine prospectively the influence of exposure to job insecurity during working life on subjective well-being (SWB) after retirement, an association which has not been studied to date. METHOD: Data were derived from the prospective population-based MONICA/KORA study conducted in southern Germany. Participants were recruited and data were collected during three independent surveys between 1984-1995 (T1) and followed up in 2009 (T2). The study sample consisted of 1801 employed participants (1146 male/ 655 female) aged 41-72 years at T1 and ≥65 years at T2, without missing data. Self-administered questionnaires and clinical examinations were used to assess job insecurity and risk factors at T1 and SWB at T2. Mean follow-up was 19.6 years. Logistic regression analyses were performed to determine the association of job insecurity with SWB after retirement. We accounted for an extensive set of sociodemographic, lifestyle-, health- and work-related risk factors. RESULTS: At T1, 39.5% of the participants reported job insecurity, which was associated with a 1.40-fold [95% confidence interval (95% CI) 1.08-1.82] risk of low SWB at T2 in models adjusted for sociodemographic and lifestyle- and health-related conditions at T1. Additional adjustment for a set of work-related risk factors at T1 had little effect on this association. CONCLUSIONS: Exposure to job insecurity at midlife was associated with low SWB in retirement, even after controlling for an extensive set of risk factors. This shows that the negative effects of unstable working conditions might persist well into retirement, long after cessation of employment.